Studies on melt processable biocomposites of polylactic acid - Joseph, Seena; Deenadayalan, E.; Mahanwar, Prakash A. (Journal of Polymers and the Environment, 2015)
Melt processable microcrystalline cellulose (MCC)/poly(lactic acid) (PLA) composites were successfully prepared by twin-screw extrusion. Several characterization techniques were used to investigate the effect of MCC on rheological behavior, morphology, crystallization and melting behavior of the PLA and structure-property correlation of the MCC/PLA composites has been established. Rheological measurements showed that the addition of MCC has a dramatic influence on the low frequency relaxations of PLA chains and above 5 % of MCC, it forms percolated network structure. Differential scanning calorimeter analysis showed that MCC acted as nucleating agent enhancing crystallization below the percolation concentration. Properties of MCC/PLA composites have been compared with that of talc and CaCO3 filled composites. Talc is found to be more effective in crystallizing PLA than MCC and CaCO3. MCC/PLA composites are found be melt processable like that of talc and CaCO3 filled PLA composites.
Keywords: Biopolymers; composites; Rheological properties; Structure-property relationship

Self-assembly of novel Fmoc-cardanol compounds into hydrogels - analysis based on rheological, structural and thermal properties - Kadeeja, Aliya; Joseph, Seena; Abraham, Jancy Nixon (Soft Matter, 2020)
Hydrogels of low molecular weight molecules are particularly appealing for various biomedical applications such as drug delivery, tissue engineering, and antitumor therapy due to their excellent biocompatibility, biodegradability, and easy availability. Fmoc-peptide hydrogels form an essential category of these hydrogels. Herein we report a new class of Fmoc hydrogels in which cardanol (3-pentadecyl phenol (PDP)) is covalently linked with fluorenylmethyloxycarbonyl group. Cardanol is a plant-based renewable raw material, readily obtained from Cashew Nut Shell Liquid (CNSL). The long aliphatic chain of pentadecyl phenol helps in bringing a structural incompatibility and generates different nanostructures such as nanospheres, nanotapes, and nanofibers depending on Fmoc substitution and the solvents used. Stable hydrogels were formed from Fmoc-PDP in DMSO/H2O, and the critical aggregation concentration (CAC) and critical gelation concentration (CGC) were determined. The role of non-covalent forces such as hydrogen-bonding, hydrophobicity, and pi-pi stacking interactions in governing self-assembly to hydrogel formation was studied for Fmoc, DiFmoc and Boc groups attached to PDP. The thermal properties were analyzed, and smectic and nematic phases were identified for the molecules depending on the substitutions involved. Overall the study supports the mechanisms of aggregation and gelation in novel Fmoc-cardanol derivatives.